In-situ gel bases ocular delivery system of Ganciclovir, in-vivo and in-vitro investigation - Susanta Paul; Subhabrota Majumdar; Mainak Chakraborty; Swarupananda Mukherjee; Nilanjan Sarkar; Bhupendra Prajapati; Nemat Ali; Abdullah F. AlAsmari; Shamama Nishat (BMC Pharmacology and Toxicology)
Abstract Ocular drug delivery is challenging due to the eye’s unique anatomy and physiology, which limit drug absorption and distribution. Traditional methods like eye drops have poor bioavailability and often require frequent dosing. In-situ gel systems, liquid formulations that transform into a gel upon contact with physiological conditions (pH, temperature, or ions in tear fluid), offer several advantages for ocular drug delivery. Ganciclovir was incorporated into a thermoresponsive in situ gel base. Nine formulations were prepared using the cold technique and a 3² full factorial design. The physical properties of ganciclovir gel, including clarity, pH, viscosity, gelation temperature, and gelation time, were scrutinized. In vitro drug release was assessed using a dialysis membrane method, and ocular toxicity was evaluated in a rabbit model. Poloxamer 407 and HPMC E-50 LV were used to prepare the gel, with the 3² factorial design analyzing the effects of varying concentrations on the gel’s viscosity, gelation temperature, and gelation time. The optimized in-situ gel formulation (Batch B5) contained 15% w/v poloxamer 407 and 1% w/v HPMC E-50 LV, achieving a viscosity of 64.81 cPs, with a gelation temperature of 39.0 °C and a gelation time of 183 s. This formulation demonstrated better permeability and sustained ganciclovir release than a commercial formulation. Ocular toxicity studies confirmed that the formulation was non-irritating and well-tolerated. Overall, the gel showed suitable physical properties, sustained drug release over 12 h, and significant potential for enhancing drug bioavailability and treatment efficacy for ocular infections. These findings confirm that the optimized ganciclovir in situ gel preparation improves eye permeation and prolongs ocular retention time, thus enhancing its therapeutic efficacy. Its sustained release and prolonged retention time make it a promising alternative to conventional eye drops, offering better patient compliance and efficacy. Graphical Abstract